From watchdog to catalyst: How emotional intelligence, organizational culture, and training drive auditor performance in Indonesia’s inspectorate general - Nugroho, Kelik (Journal of Economics and Business Letters, 2025)
This study tests a governance-grounded model in which emotional intelligence (EI), organizational culture (OC), and education–training (Diklat) jointly predict auditor job performance within the Inspectorate General of the Indonesian Ministry of Religious Affairs. Using a cross-sectional explanatory survey of 92 government auditors, we measured EI (self-awareness, self-regulation, motivation, empathy, social skills), OC (integrity, discipline, learning orientation, team/people focus), Diklat (relevance, delivery, instructor quality, facilities), and performance (ability, initiative, timeliness, quality, communication) on five-point Likert scales, with supervisor input to reduce common-method bias. All instruments demonstrated strong reliability (α = .909–.965) and satisfactory validity. Bivariate regressions showed large positive effects on performance for EI (R² = .693), OC (R² = .654), and Diklat (R² = .756). In a joint OLS model, all predictors remained significant with standardized coefficients: Diklat (β = .497, p < .001), EI (β = .346, p < .001), and OC (β = .155, p = .044), indicating training has the largest unique contribution once shared variance is partialled out. Practically, results argue for practice-embedded, EI-aware training; culture-by-design that emphasizes discipline and values-based decisions; and systematic follow-up on audit recommendations. The findings reinforce the shift of internal audit from watchdog to consultant and catalyst, linking human-system levers to auditable improvements in public-sector governance. Limitations include cross-sectional design and potential construct overlap; future research should adopt lagged measures and objective performance indicators.